Association between regional deprivation and type 2 diabetes incidence in Germany - Ralph Brinks; Annika Hoyer; Wolfgang Rathmann; Esther Jacobs; Thaddäus Tönnies (BMJ Open Diabetes Research & Care)
Objective The aim of this analysis was to estimate the association between regional deprivation and type 2 diabetes incidence and to investigate differences by age and sex for Germany.Research design and methods Type 2 diabetes incidence rate ratios comparing the most deprived fifth of the population to the remainder of the population (divided into quintiles) were estimated using the illness-death model, which describes the relationship between prevalence, mortality, and incidence. For the analysis, we used the type 2 diabetes prevalence and the general mortality rate according to deprivation quintiles, which we calculated based on valid estimates for Germany. Because mortality rate ratios for people with type 2 diabetes compared with people without type 2 diabetes are lacking for Germany, we used estimates from Scotland. Estimates were standardized to the German population in 2012 and stratified by sex.Results Incidence of type 2 diabetes was estimated to be over twice as high among people living in the most deprived regions of Germany compared with people living in the least deprived regions (men: 2.41, 95% CI 1.27 to 4.28; women: 2.40, 95% CI 1.25 to 4.29). The strength of the association increased with increasing age until the age of 75 years. No sex differences were present.Conclusions The study adds new evidence regarding the association between type 2 diabetes incidence and regional deprivation for Germany. The results underpin the importance to intensify public health actions to reduce social inequalities in Germany and whole Europe in the future.